Different approaches for making the initial selection of talented students in programming competitions - Kostadinov, Bojan; Jovanov, Mile; Stankov, Emil; Mihova, Marija; Risteska Stojkoska, Biljana (Vilnius University Press, 2015)
Competitions in informatics are one of the most useful ways of engaging pupils to the field of computer science. Many national and international competitions are carried out each year, with the organizers of each of them attempting to reach out to as many potential students as possible. In this paper, we analyse several different contest types, how each of them aids to promote computer science by engaging students in competitions, and how they can help provide the initial selection of talented students for the later stages of the competitions. Based on that, we propose seven criteria for the classification of the contests. Further we present our rich experience in the organization of Macedonian contests. Finally, we propose different approaches for making the initial selection of talented students in programming competitions and discuss ways for alleviating some of the issues with standard contests, for example enabling feedback and introducing difficulty divisions.
Keywords: programming contests, types of contests, promoting informatics, identifying talented students